2017
DOI: 10.1017/aer.2017.109
|View full text |Cite
|
Sign up to set email alerts
|

Influence analysis of propeller location parameters on wings using a panel/viscous vortex particle hybrid method

Abstract: For aircraft that employ distributed propeller propulsion systems, the distributed propeller slipstream increases the analysis complexity. The objective of this paper is to rapidly analyse the influence of propeller slipstream on a wing using a fast prediction approach to perform conceptual design studies. This fast approach is implemented through a panel/viscous vortex particle hybrid method taking into account the air viscosity effect. The parametric studies of propeller streamwise, spanwise, vertical instal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 28 publications
(39 reference statements)
0
5
0
Order By: Relevance
“…VPM has been successfully applied to a variety of wake-dominated flow, [8][9][10][11][12][13][14][15][16] especially the cases of coaxial rotors 17,18 and rotorcraft forward flight. [19][20][21][22][23] However, it has not yet been applied to the coplanar multirotor configuration.…”
Section: Introductionmentioning
confidence: 99%
“…VPM has been successfully applied to a variety of wake-dominated flow, [8][9][10][11][12][13][14][15][16] especially the cases of coaxial rotors 17,18 and rotorcraft forward flight. [19][20][21][22][23] However, it has not yet been applied to the coplanar multirotor configuration.…”
Section: Introductionmentioning
confidence: 99%
“…For the purpose of utilizing the suction effect ahead of the propeller, it is better that the propeller is placed above the wing, which is called over-the-wing (OTW) propeller configuration [25][26][27]. The experimental result demonstrates that the OTW configuration has an excellent advantage of reducing the wing drag through the propeller blade suction compared with a tractor propeller arrangement, while its lift enhancing capability is slightly weaker than the latter.…”
Section: Fuel Saving Double Channel Wing Configurationmentioning
confidence: 99%
“…Numerical studies using the vortex panel-particle hybrid method have also been used to analyze the influence of propeller slipstream on a wing [13]. A numerical study on the performance of tip-mounted propellers using a one-equation RANS model showed that the use of the actuator disk model for studying the slipstream-wing interaction reduces the computational cost by 85% [14].…”
Section: Introductionmentioning
confidence: 99%